Análise dos indicadores econômico-financeiros das Farmácias Pague Menos - Austregésilo Neto, José Israel Cintra (2016)
Competitiveness among retail organizations is increasing as time goes by, more and more companies are looking to work better to be able to serve their current customers and prevent them from being lost to the competition. This has raised the need to expand the business because over time the markets are getting saturated and so it is important to seek to reach the potential customers not yet explored. For the expansion of an organization to be solid and healthy, it is necessary to understand how its financial structure is and to identify, its economic indicators to know if it is possible its own financing or if it is necessary to enter third-party capital to subsidize the operation, and still if the company is able to bear the cost of this external capital. In this way, the present work aims to carry out a situational study of the company focus through the analysis of its main financial statements. The research is specifically aimed at the pharmaceutical retail company Pague Menos. It was carried out a bibliographic study on financial analysis and economic indicators that subsidized the case study that was done about the company focus. The analysis of the indicators calculated based on the financial statements published by the organization indicates that although its indebtedness is not low and that there are even some problems in its operation, it can be said that its growth is solid and that its financial situation is healthy.